An Unusual Case of Pulmonary Nocardiosis in Immunocompetent Patient - Zehra Yaşar; Murat Acat; Hilal Onaran; Mehmet Akif Özgül; Neslihan Fener; Fahrettin Talay; Erdoğan Çetinkaya (Case Reports in Pulmonology)
Pulmonary nocardiosis is a subacute or chronic necrotizing pneumonia caused by aerobic actinomycetes of the genus Nocardia and rare in immune-competent patients. A 35-year-old male, who had treated with antituberculosis drugs, presented with cough, dyspnea, and expectoration with episodes of hemoptysis with purulent sputum. The diagnosis of nocardiosis was made by microscopic examination of the surgically resected portion of the lung and revealed filamentous Gram-positive bacteria.